Docility and desert: Government discourses of compassion in Australia's asylum seeker debate - Peterie, Michelle (Journal of sociology (Melbourne, Vic.), 2017)
In the years since 2001, Australian governments on both sides of politics have at times appealed to compassion to justify their asylum seeker policies. This article takes these discourses of compassion - contradictory and cynical as they sometimes seem - and subjects them to careful and systematic analysis. It seeks to identify the underlying model of compassion that these government discourses employ, and to explain its significance. Ultimately it argues that the model of compassion that has been advanced by successive Australian governments deviates from traditional philosophical understandings of the concept. In reserving compassion for the weak and the passive, government discourses have allowed Australia to understand itself both as 'good' and as powerful. When privilege replaces solidarity as the basis for compassion, discourses of compassion - like the 'hardline' rhetoric that scholars have often prioritised in their analyses - speak to the fears and insecurities of the Australian people.